Interoperabilitas: Konsep, Implementasi, Dan Tantangan Dalam Era Transformasi Digital - Maulana, Sandi Agus (Journal of Comprehensive Science, 2025)
Interoperability has become a crucial element in digital transformation, enabling different systems and applications to effectively exchange information. This article presents the results of a literature review aimed at examining the concepts, dimensions, and challenges of implementing interoperability within the context of modern digital environments. Primary sources include international journals such as Hodapp & Hanelt (2022), Scheibner et al. (2021), and national studies from the public sector (Fajar, 2023; Siregar & Nasution, 2023). Thematic analysis reveals that interoperability involves technical, semantic, organizational, and cultural aspects. Key challenges include gaps in standards, organizational cultural resistance, limited infrastructure, and inadequate regulations. This study suggests that the development of adaptive interoperability models, supported by digital governance and education, should become a focal point for future research and policy.